How Knowledge on Microbiota may be Helpful to Establish an Optimal Diet for Health Maintenance - Paolo, Mainardi; Paolo, Carta; Michele, Mainardi; Pasquale, Striano (International Journal of Nutrition, 2018)
In the last few years, gut microbiota has been identified to be an essential mediator in health and disease. In fact, it interacts with various organs and systems in the body, including brain, lung, liver, bone, cardiovascular system, and others. Microbiota-derived metabolites such as the short chain fatty acid (SCFA) butyrate are primary signals, which link the gut microbiota and physiology. Then, the findings on the roles of microbiota profoundly change not only the key concepts of biology and medicine, but also of nutrition. In fact, it is currently evident how the main task of nutrition is not to nourish us, but to maintain a comfortable environment for the intestinal microbiota. In this way, it works in symbiosis with us, correctly controlling the functioning of the organs, the physiological parameters and the cellular regenerative processes. It is also evident that the strength of reparative processes correlates with the ability of digestive system to process complex foods, which increases during weaning, a period of time in which the diversity of bacterial strains increases. Therefore, a task of food is to keep trained the digestive system, to which it corresponds an high microbiota diversity. Elderly leads to reduced microbiota diversity to which corresponds an intestinal frailty, responsible for the frailty of the elderly. In conclusion, a correct diet may not only keep us in good health but may also guarantee us longer longevity.
Keywords: microbiota; Taste Receptors; evolution; short chain fatty acids; alpha-lactalbumin